Optimasi Rute Distribusi Logistik Bencana Tsunami Aceh Menggunakan Algoritma Ant Colony Optimization (ACO) - Susila Bahri; Alti Vanie Diandra Eka Putri; Azzah Marsa Amalia; Dea Andini; Lelen Purnama Sari; Bayu Anugrah; Muhammad Hasbi Ahzani (Mandalika Mathematics and Educations Journal, 2026)
This study aims to optimize the tsunami disaster logistics distribution route in Aceh Province by using the Ant Colony Optimization (ACO) algorithm combined with parameter tuning. Aceh is an area with a high level of earthquake vulnerability, making it prone to tsunamis such as the one that occurred in 2004, thus requiring a fast and efficient logistics distribution system. The Aceh Logistics Building was designated as the distribution center, while nine evacuation points from the evacuation route map of the Banda Aceh City GIS Technical Implementation Unit (UPTB) were used as destination points. The distances between points were calculated using Google Maps and arranged in a distance matrix. Parameter tuning was performed using the Grid Search method through MATLAB to determine the shortest route. The results of the study show that the minimum total distance obtained is 664.3 km to reach all evacuation points and return to the logistics warehouse. This value is smaller compared to the route before the parameter tuning process, indicating an improvement in distribution efficiency. Therefore, the implementation of the ACO algorithm combined with the Grid Search method is able to produce a more optimal route and support faster and more targeted logistics distribution in emergency conditions.